Is Anyone Listening? Citizen Participation and The Illusion of Democracy in A Peru Regional Government - Montoro, Ronald Ivan Vasquez (Departemen Ilmu Administrasi FISIP UNHAS, 2025)
This research examines the link between citizen participation and public decision-making in an entity of the public sector in the province of Paita in Peru, in 2024. The research is based on the premise that democratic governance, good public administration, and sustainable development require the involvement of citizens. The research has a non-experimental, descriptive, quantitative design. Information was obtained from questionnaires and interviews of 200 citizens and 40 municipal officials. The research analyzes citizens' participation and the decision-making process, and their dimensions, in the light of commitment, surveillance, and oversight, in the case of participation; and immediate response, effective decisions, and resolution of difficulties, in terms of decision-making. The results suggest that the citizens are